ATTRACTING FOREIGN INVESTMENTS TO THE REPUBLIC OF UZBEKISTAN FOR ENTREPRENEURSHIP AND BUSINESS DEVELOPMENT (Proceedings of International Educators Conference, 2023)
In this article, we will discuss how to attract foreign investments to business and entrepreneurship projects planned to be established in the Republic of Uzbekistan. Also, in this article, we will mention various positive cases after investments in entrepreneurship and business projects in the Republic of Uzbekistan.